Nieznane kazanie(?) polskie z około połowy XV wieku. Ze zbiorów gnieźnieńskich - Łukaszewski, Jakub; Wydra, Wiesław (Biblioteka Jagiellońska, 2016)
The article presents a hitherto unknown Polish text which was written on one sheet of paper about the middle of the fifteenth century and which was recently discovered in the Archive of the Archdiocese of Gniezno (Ms. Fragm. 312). It is all that remains of some larger manuscript which was written very carefully in Polish. Given the small size of the text, it is very difficult to identify its literary genre. Most likely it is a passage from an erudite sermon or some other penitentiary work.
An Unknown Polish sermon(?) from ca. 1450. From the Gniezno collection
W artykule przedstawiono nieznany dotychczas tekst polski z około połowy XV wieku. Znajduje się on na jednej karcie znalezionej w Archiwum Archidiecezjalnym w Gnieźnie (Ms. Fragm. 312). Tekst jest fragmentem jakiegoś większego rękopisu w języku polskim, bardzo starannie sporządzonego. Niewielkie rozmiary tekstu utrudniają jego gatunkową identyfikację, prawdopodobnie jest to urywek intelektualnego kazania lub jakiegoś dzieła penitencjalnego.
Keywords: sermon; manuscript; fragmentology; Polish literature; fragment rękopisu; kazanie